The Effect of Light Physical Exercise and Relaxation Techniques on the Cardiovascular Health of Elderly People with Hypertension: Efektifitas Isometric Handgrip Exercise dan Slow Deep Breathing dalam Mengendalikan Hipertensi : A Systematic Review - Tifany Hayuning Ratri; Lia Fadlilah (Poltekkes Kemenkes Malang, 2026)
Abstract: Background: High Blood Pressure is still a global health problem. Non-pharmacological efforts such as handgrip exercise and slow deep breathing (SDB) can lower blood pressure. Objective: To determine the effectiveness of a combination or each of these exercises in lowering blood pressure in hypertension sufferers. Methods: A systematic review was identified in three databases Google Scholar and Pubmed (2020–2025) using the search terms “Hypertension OR Blood Pressure AND Elderly AND Handgrip Exercise AND Slow Deep Breathing.” Risk of bias assessment using JBI Critical Appraisal Tools. Data were extracted by researchers and analyzed using thematic analysis. Results: 1,070 articles after duplicate removal and screening obtained 280 reports to be retrieved 90 articles were assessed for eligibility in depth then 10 articles were selected for review using PICOT, Isometric handgrip exercise intensity 30% MVC for 8–20 weeks is effective in reducing systolic blood pressure (SBP) significantly. SDB exercise of 6 breaths per minute showed a decrease in SBP of up to 18.17 mmHg through increased parasympathetic activity and baroreceptor stimulation. Conclusion: There is a decrease in blood pressure in patients with stage one hypertension. Future researchers are expected to examine the young age group to see the effectiveness of early hypertension prevention considering the increasing trend of cases in productive age.